ANALISIS EFEKTIVITAS PENERIMAAN RETRIBUSI IZIN MENDIRIKAN BANGUNAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA MEDAN - Tengku Eka Susilawaty; Nurul Izzah Lubis; Citra Windy Lubis (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This research aims to determine the level of effectiveness in receiving Building Permit Retribution and its Contribution to Medan City Regional Original Income. This research uses quantitative descriptive data analysis techniques. Using secondary data sources in the form of documentation, namely by viewing and using reports and records in the Medan City Investment and One-Stop Integrated Licensing Services Service (DPMPTSP). The results of the research show that the effectiveness of Medan City Building Permit (IMB) Retribution Receipts in 2020 and 2021 is in the very effective criteria even though in 2019 and 2022 it was not effective. Meanwhile, the contribution of Building Permit Levy (IMB) to Original Regional Income (PAD) in Medan City from 2019 - 2022 is very low.